THE IMPACT OF RAJPUT ARCHITECTURE STYLE ON CONTEMPORARY RESORT DESIGN IN JAIPUR RAJASTHAN - Vinod Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the development of Rajput architecture design giving shape to examining the historical factors, in the broader context of the Rajputana region in medieval India. By researching the socio-political landscape, cultural influences, distinctive architectural features, conservation system, regional variations, cultural Content of medieval socio-political influences, and distinctive conservation Variations, this research on the Rajput dynasty's rich architectural heritage provides an understanding of the broader. Building on this historical foundation, Studies in contemporary resort design of analysis the incorporation of Rajput architectural elements such as arches, domes, Jharokha, chhatri, and Lattice work. Through qualitative analysis and case studies, this research examines the impact of these elements on aesthetics, utility, and guest experiences in modern resorts. This study bridges the gap between historical and modern design, Rajput architecture of permanent relevance, and contemporary architecture of landscapes giving shaped the role of intense appreciation having contribution.